If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying N + 4 = 3n + 16 Reorder the terms: 4 + N = 3n + 16 Reorder the terms: 4 + N = 16 + 3n Solving 4 + N = 16 + 3n Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + N = 16 + -4 + 3n Combine like terms: 4 + -4 = 0 0 + N = 16 + -4 + 3n N = 16 + -4 + 3n Combine like terms: 16 + -4 = 12 N = 12 + 3n Simplifying N = 12 + 3n
| -5t^2+40t+20= | | 0.2r-1.3r+0.6=-0.9+3.6 | | 19/2/3 | | 2/3/18 | | 2k+2=-13+3k | | X+0.6x+0.03x=500 | | 1/5-1/6z=7/6 | | N-9=9+15 | | 4(3z+5)=10-2(z-5) | | 121^-1/2 | | 426=350t | | 2(1-7y)=4y+3 | | T-5+7+2k-3k=k-8 | | 6y+7=10y-3 | | 462=370x | | (36x^2y^4)^1/2 | | 4(3z-1)-3(z-8)=3(z-1) | | (T-2)/(4-t) | | -9+10x=4x+15 | | 9=12x^2-23x | | -77.08=9.4y | | 2x-1-4=0 | | -0.56m=4.592 | | 2.3x=14.582 | | 2c+4=14 | | 5/6z-100 | | 13-6m=4-6m | | 3^4/5*3^3/x | | 11k=13t-7k/2t | | 6b^2+48b=0 | | -243=-9(10+n) | | 2x-4-(12+4x)=3x |